Advantages of using reduced-volume intensity modulated radiation therapy for the treatment of nasopharyngeal carcinoma: a retrospective paired study - Fang Liu; Ting Luo; Tao Jin; Jiahui Zhang; Zhongzheng Xiang; Ruonan Yan; Li Xie; Xin Wu; Hong Zhang; Feng Wang; Ping Li; Lei Liu (BMC Cancer, 2019)
Abstract Background The definition of clinical target volume (CTV) in intensity modulated radiation therapy (IMRT) for nasopharyngeal carcinoma (NPC) has not been addressed. We performed this study to assess the feasibility and efficacy of using IMRT with reduced-volume CTV for the treatment of nasopharyngeal carcinoma. Methods We retrospectively reviewed 293 non-metastatic NPC patients treated with IMRT from 2002 to 2013. A total of 180 matched cases finally included with 90 received conventional-volume IMRT (CV-IMRT) and 90 received reduced-volume IMRT (RV-IMRT). Kaplan-Meier method and log-rank tests were used to compare NPC-specific survival. Multivariate analyses using the Cox proportional hazards model were conducted to detect independent predictors. Results With a median follow-up of 70 months, the 3-year overall survival, progression-free survival, distant metastasis-free survival, local recurrence-free survival, regional recurrence-free survival, locoregional recurrence-free survival rates were 88.9, 84.4, 92.2, 91.1, 98.9, 91.1% for the CV-IMRT arm and 92.2, 85.6, 90.0, 93.3, 98.9, 93.3% for the RV-IMRT arm, respectively. None significant survival difference was observed. Additionally, RV-IMRT was associated with reduced risk of late xerostomia (P = 0.039) and hearing loss (P = 0.008), compared versus CV-IMRT. Conclusions The use of RV-IMRT for the treatment of NPC led to comparable survival condition and truly reduced toxicity reactions compared versus CV-IMRT.